Treatments Outcomes in Histological Variants and Non-Urothelial Bladder Cancer: Results of a Multicenter Retrospective Study - Epaillard, Nicolas; Parent, Pauline; Loriot, Yohann; Lavaud, Pernelle; Vera-Cea, E-B.; Martinez-Chanza, Nieves; Rodriguez-Vida, Alejo; Dumont, Clement; Lozano, Rebeca; Llácer, Casilda; Ratta, Raffaele; Oudard, Stephane; et al. (Frontiers in Oncology, 2021)
Introduction: Less than one-third of bladder cancers are non-pure urothelial carcinoma [with variant histological (HV) or non-urothelial carcinoma (non-UC)] for which no treatment guidelines are available. We aim to evaluate the efficacy of systemic treatments in VH or non-UC bladder cancers. Material: Multicenter retrospective analysis of patients treated for advanced or metastatic VH or non-UC bladder cancers. Primary endpoint was overall response rate (ORR) according to treatment line, regimen and histology subtype. Secondary endpoints were progression-free survival (PFS) and overall survival (OS). Results: Between 2005 and 2020, 46 patients from seven centers were included. The median age was 66 years (58.75; 74.75), 65.2% were male and 67.2% presented HV. At first line, the ORR for the entire population was 54.4% and median OS was 21.6 months (95% confidence interval [CI]: 14.2-38.6). The ORR of the 37 patients treated with chemotherapy at first line was 62.2% with median PFS and OS of 7.3 (95% CI: 4.5-8.6) and 21.6 months (95% CI: 14.2-35.7), respectively. Dose dense MVAC and platinum doublet chemotherapy had the highest ORR (71.4% and 65.2%). The 9 patients treated with immunotherapy at first line had an ORR of 22.2%, a median PFS of 3.3 months (95% CI:2.3-NR) and the median OS was not reached (95% CI:13.8-NR). Response to treatment varied depending on the histological sub-types and on the treatment type. Conclusion: Chemotherapy and immunotherapy have shown to be effective in VH or non-UC cancers, a rare histological subtype for which we currently have very little data in the literature.